Prognostic biomarker DARS2 correlated with immune infiltrates in bladder tumor - Yang, Hailang; Ma, Li; Deng, Wen; Fu, Bin; Nie, Jianqiang; Liu, Xiaoqiang (Frontiers in Immunology, 2024)
Background： DARS2 is a pivotal member of the Aminoacyl-tRNA synthetases family that is critical for regulating protein translation. However, the biological role of DARS2 in bladder cancer remains elusive.We analyzed the correlation between DARS2 expression and prognosis, tumor stage, and immune infiltration in bladder cancer using The Cancer Genome Atlas(TCGA) database. We validated findings in clinical samples from The First Affiliated Hospital of Nanchang University and explored the biological functions of DARS2 using cell and animal models.We found DARS2 to be upregulated in bladder cancer, associated with tumor progression and poor prognosis. Immune infiltration analysis suggested that DARS2 may facilitate immune evasion by modulating PD-L1. Cell and animal experiments validated that DARS2 knockdown and overexpress can inhibit or increase cancer cell proliferation, metastasis, tumorigenesis, immune escape, and PD-L1 levels.Conclusions： Our study reveals DARS2 as a potential prognostic biomarker and immunotherapy target in BLCA.